Causes of hospital readmission after heart surgery - Bárbara Rodrigues Nunes Barreiros; Estela Regina Ferraz Bianchi; Ruth Natalia Teresa Turrini; Vanessa de Brito Poveda (Universidade Federal de Goias, 2016)
The objective was to identify readmission's profile and causes of  heart surgery patients. A retrospective, descriptive study, through the revision of records from patients submitted to myocardial revascularization surgery or valvar prosthesis implantation with posterior readmission. Sixty-two patients composed the sample. The readmission rate was 5.9%. Surgical site infection was the main cause for readmission in 87.5% of patients submitted to myocardial revascularization surgery and in 12.5% of valvar implantation (p<0.001) and, it was associated with obesity (p=0.05) and dyslipidemia (p=0.007). To identify patients at risk of surgical site infection can minimize readmission rates and decrease care costs and, it deserves a special planning of multi-professional actions.